2004
DOI: 10.1098/rsbl.2003.0138
|View full text |Cite
|
Sign up to set email alerts
|

Predator–prey coevolution: Australian native bees avoid their spider predators

Abstract: Australian crab spiders Thomisus spectabilis manipulate visual flower signals to lure introduced Apis mellifera. We gave Australian native bees, Austroplebia australis, the choice between two white daisies, Chrysanthemum frutescens, one of them occupied by a crab spider. The colour contrast between flowers and spiders affected the behaviour of native bees. Native bees approached spideroccupied flowers more frequently. However, native bees avoided flowers occupied by spiders and landed on vacant flowers more fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 18 publications
0
48
1
Order By: Relevance
“…In contrast to European honeybees, stingless native Australian bees (Australoplebia australis) are not deceived by white T. spectabilis (Heiling and Herberstein, 2004b). They can detect white spiders on flowers and avoid them.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to European honeybees, stingless native Australian bees (Australoplebia australis) are not deceived by white T. spectabilis (Heiling and Herberstein, 2004b). They can detect white spiders on flowers and avoid them.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in solitary bees, there is a very tight link between foraging efficiency, predator avoidance and fitness [13]. As a result, bees have evolved predator-avoidance strategies [3,[14][15][16][17][18] and respond to the trade-off between minimizing predation risk and maximizing foraging efficiency [19]. Furthermore, it is known that chemical information plays an important role in risk assessment: the response of bees to ambushing crab spiders changes when chemical cues are removed [20], and social bees release alarm pheromones to mark flowers where a predator is hidden [14,21].…”
Section: Introductionmentioning
confidence: 99%
“…Different species of pollinators respond differently to the presence of crab spiders (Brechbühl et al, 2009;Brechbühl et al, 2010) and some prey species are attracted to the high UV contrast (Heiling and Herberstein, 2004;Heiling et al, 2003;Llandres et al, 2011). In this scenario, one would expect that in 2008 the most common prey were those attracted to conspicuous UV-bright spiders, but the most common prey in 2009 were not.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, one would expect that in 2008 the most common prey were those attracted to conspicuous UV-bright spiders, but the most common prey in 2009 were not. For example, honeybees are attracted and land more frequently on flowers harbouring UV-bright F. M. Gawryszewski, A. L. Llandres and M. E. Herberstein spiders (Herberstein et al, 2009), but Australian native bees are less likely to land on such flowers (Heiling and Herberstein, 2004;Llandres et al, 2011, the most common prey were honeybees, the best strategy would be to adopt a high UVreflectance strategy, whereas if in 2009 the most common prey were native bees, the most efficient strategy would be to reduce conspicuousness. In our experiment on the effect of background colouration and food intake on spider colouration, we found that the spiders have the ability to change colour independently of food intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation